O mercado futuro de dólar da BM&FBOVESPA: uma análise de dependência sob a ótica da teoria de cópulas - Silva, Murilo Massaru da (2013)
Considering the high integration degree of the world financial market, this paper attempts to model the dependence relationship between the BM&FBOVESPA U.S. Dollar futures market and the U.S. economy, using the Copula framework. The U.S.Dollar future contract negotiated on the Brazilian futures market is one of the top five futures contracts with the highest negotiation volume of the world and, hence, it plays a fundamental role in the Brazilian financial market. After the estimation of several families of copulas it was shown that the t-student copula is appropriated to model the dependence between the analyzed variables. Furthermore, the realized statistics tests rejected hypothesizes of independence and extreme value dependence. This study concludes that the variables present a moderate negative dependence, even considering that it is about different kind of markets from distinct countries.